Analysis of The Effect of Linear and Non-Linear Loads against The Quality of Power at The Power Converter - Anicetus Damar Aji; Kusnadi Kusnadi (IPTEK Journal of Proceedings Series, 2014)
Application of the linear and non-linear loads are widely used in household industries, office buildings and factories such as the power converters for motor speed control ac / dc. Un-interruptible power supplies (UPS). A fluorescent lamp with the electronic ballasts. If the use of linear and non-linear loads in power converters are based electronics will result in the power quality on electrical power distribution system will be worse.  The power quality is affected by the value of the current or the voltage harmonics. The research in Electrical laboratory conducted to evaluate the power quality due the use of linear and non-linear loads in the form of the value of THD% (Total Harmonic Distortion), the power factor and harmonic waves that arise in three-phase power converter and will be measurement by using the LAB-VIEW 8.5. The research are expected to result in variations of the value of the harmonics and power factor is a measure of power quality, to load in the form of linear likes lighting and non-linear loads such as motor loads or the other inductive loads.